Cost–effectiveness of rivaroxaban versus heparins for prevention of venous thromboembolism after total hip or knee surgery in Sweden. (October 2011) - Ryttberg, Lars; Diamantopoulos, Alex; Forster, Fiona; Lees, Michael; Fraschke, Anina; Björholt, Ingela
Aims: The objective of this study was to evaluate the cost–effectiveness of rivaroxaban versus the low-molecular-weight heparins (LMWH) enoxaparin and dalteparin for the prevention of venous thromboembolism (VTE) after total hip replacement and total knee replacement in Sweden.Methods: The model included acute venous thromboembolic events and long-term complications over a 5-year time horizon represented by an acute and a chronic phase with 1-year cycles. Transition probabilities were derived from the Regulation of Coagulation in Orthopaedic Surgery to Prevent Deep Vein Thrombosis and Pulmonary Embolism (RECORD) clinical trials.Results: In patients undergoing total hip replacement, the incremental cost per additional quality-adjusted life-year of extended prophylaxis for 35 days with rivaroxaban versus 14 days of prophylaxis with enoxaparin or dalteparin was SEK29, 400 and SEK35, 400, respectively. In total knee replacement patients, 14 days of rivaroxaban dominated 14 days of LMWH as prophylaxis for VTE.Conclusion: The results of the economic model consistently showed that, over a 5-year period, rivaroxaban is a cost-effective alternative to 14 days of LMWH for VTE prophylaxis in Sweden.